Handbook of labour market policy in advanced democracies - Clegg, Daniel; Durazzi, Niccolo (Edward Elgar Publishing, 2023)
"Bringing together contributions from leading labour market policy scholars from across the globe, this state-of-the-art Handbook offers extensive and compelling analyses of labour market policy in advanced democracies. Drawing on the lively debates on labour market policy that have characterised comparative social policy and comparative political economy scholarship in recent years, the Handbook provides theoretical insights into the core concepts, changing contexts and main actors that shape contemporary labour market policy. Using macro-regional case studies spanning Asia, Australasia, Europe and North America, it offers detailed empirical illustrations of how major labour market policies and institutions have evolved over time and across countries. Chapters further examine the diversity of policy options and their various political implications, assessing the relationship between labour market policy and major socio-economic outcomes, such as inequality, well being and political participation. Integrating cutting-edge theory with rich empirical insights, this incisive Handbook will be an invaluable reference for students and scholars of comparative social policy and comparative political economy. Its comprehensive coverage will also allow policy-makers and practitioners to reflect critically on the role of labour market policy in today's complex societies"--
Includes bibliographical references and index
Keywords: Demokratie; Politische Ökonomie; Arbeitsmarktpolitik